2013
DOI: 10.1111/hsc.12046
|View full text |Cite
|
Sign up to set email alerts
|

‘It ain't what you do it's the way that you do it’: lessons for health care from decommissioning of older people's services

Abstract: Public sector organisations are facing one of the most difficult financial periods in history and local decision-makers are tasked with making tough rationing decisions. Withdrawing or limiting services is an emotive and complex task and something the National Health Service has always found difficult. Over time, local authorities have gained significant experience in the closure of care homes - an equally complex and controversial issue. Drawing on local knowledge and best practice examples, this article high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 18 publications
(24 reference statements)
1
28
0
Order By: Relevance
“…A range of theoretical approaches to facilitate implementation of disinvestment decisions has been proposed but the authors do not report application or evaluation of these strategies in the disinvestment context. These include communication and educational materials [6, 7, 63, 70, 107, 109]; financial incentives and pay-for-performance [46, 70, 109, 126, 127]; reinvestment of resources saved [8, 18, 107, 128]; clinical champions [18, 77]; clinical pharmacists to monitor and advise prescribers [129]; quality standards [70, 127]; professional standards, maintenance-of-certification activities and practice audit [70]; prompts through guidelines, protocols, clinical pathways and decision support systems [6, 7, 24, 48, 109, 126, 127]; requirements to report variations from mandatory guidelines [127]; monitoring and reporting of outcomes [107, 109, 126]; public reporting of provider performance [70, 109, 126, 127]; training and re-organisation of staffing and equipment [107]; and “ picking low hanging fruit ” before tackling more difficult projects [18]. The Schmidt framework for disinvestment notes that both process and outcome evaluations should be undertaken but provides no other details [95].…”
Section: Resultsmentioning
confidence: 99%
“…A range of theoretical approaches to facilitate implementation of disinvestment decisions has been proposed but the authors do not report application or evaluation of these strategies in the disinvestment context. These include communication and educational materials [6, 7, 63, 70, 107, 109]; financial incentives and pay-for-performance [46, 70, 109, 126, 127]; reinvestment of resources saved [8, 18, 107, 128]; clinical champions [18, 77]; clinical pharmacists to monitor and advise prescribers [129]; quality standards [70, 127]; professional standards, maintenance-of-certification activities and practice audit [70]; prompts through guidelines, protocols, clinical pathways and decision support systems [6, 7, 24, 48, 109, 126, 127]; requirements to report variations from mandatory guidelines [127]; monitoring and reporting of outcomes [107, 109, 126]; public reporting of provider performance [70, 109, 126, 127]; training and re-organisation of staffing and equipment [107]; and “ picking low hanging fruit ” before tackling more difficult projects [18]. The Schmidt framework for disinvestment notes that both process and outcome evaluations should be undertaken but provides no other details [95].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the importance of these issues, there is little formal evidence about what happens when care homes close (Le Mesurier & Littlechild, ; Robinson, Glasby, & Allen, ; Scourfield, ). Holder and Jolley's () international review of forced relocation between nursing homes identified a possible 3,500 initial results (2000–12), but no studies about the outcomes of care home closures in the UK, and only one previous UK research team exploring closure process (Williams & Netten, ; Williams, Netten, & Ware, ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, questions about the concepts, context, settings, systems, processes and principles for disinvestment have been addressed in systematic reviews [7, 9, 13, 20–24] and other studies [8, 10, 11, 25–29] and more examples of individual projects have been published [20]. No papers discussing the concept of an organisation-wide, systematic, integrated approach to disinvestment in a health service organisation have been identified [30].…”
Section: Resultsmentioning
confidence: 99%